A four-part guide to lung immunology: Invasion, inflammation, immunity, and intervention - Gopallawa, Indiwari; Dehinwal, Ruchika; Bhatia, Vaibhav; Gujar, Vikramsingh; Chirmule, Narendra (Frontiers in Immunology, 2023)
Lungs are important respiratory organs primarily involved in gas exchange. Lungs interact directly with the environment and their primary function is affected by several inflammatory responses caused by allergens, inflammatory mediators, and pathogens, eventually leading to disease. The immune architecture of the lung consists of an extensive network of innate immune cells, which induce adaptive immune responses based on the nature of the pathogen(s). The balance of immune responses is critical for maintaining immune homeostasis in the lung. Infection by pathogens and physical or genetic dysregulation of the immune homeostasis result in inflammatory diseases. These responses culminate in the production of a plethora of cytokines such as TSLP, IL-9, IL-25, and IL-33, which have been implicated in the pathogenesis of several inflammatory and autoimmune diseases. Shifting the balance of Th1, Th2, Th9, and Th17 responses have been the targets of therapeutic interventions in the treatment of these diseases. Here, we have briefly reviewed the innate and adaptive immune responses in the lung. Further, we have elaborated on the impact of inflammatory and infectious diseases, advances in therapies, and drug delivery devices on this critical organ. Finally, we have provided a comprehensive compilation of different inflammatory and infectious diseases of the lungs and commented on the pros and cons of different inhalation devices for the management of lung diseases. The review is intended to provide a summary of the immunology of the lung, with an emphasis on drug and device development.